Effect of Curcumin-Bovine Serum Albumin Complex on the Quality of Yak Milk Cheese - Yan ZHANG; Lianhong CHEN; Li ZHANG (Shipin gongye ke-ji, 2022)
The purpose of this study was to investigate the construction of curcumin encapsulated nanocomposite based on bovine serum albumin (BSA) could be a potential strategy to improve the ripening quality of yak cheese. The moisture, ash, crude protein, crude fat, pH value, pH4.6 acetate buffer soluble nitrogen, 12% trichloroacetic acid solution soluble nitrogen, thiobarbituric acid reactant, acid value and sensory index of yak milk cheese were determined. The results showed that the presence of curcumin-BSA nanocomplex could significantly improve the moisture and protein content of yak milk cheese (P<0.05）, promote the proliferation of lactic acid bacteria and inhibit the growth of hybrid bacteria, contribute to the decomposition of fat and protein in yak milk cheese, and form short-chain fatty acids and polypeptides, presenting a good unique flavor. However, the high addition of complex would weaken the probiotic effect, reduce the decomposition efficiency of fat and protein, and also cause the cheese to turn yellow and reduce the sensory score. In the early stage of the maturation process, the sensory score was significantly improved due to the occurrence of proteolysis reaction and lipolysis reaction (P<0.05）, but too long maturation period would lead to accumulation of bitter peptides and other substances, forming bad flavors and affecting sensory quality. In general, curcumin-bovine serum albumin complex can improve the quality of yak milk cheese, and the best quality of yak milk cheese is obtained when the compound supplemental level is 4% and the maturation time is 60 d.